(untitled) (Academicia Globe: Inderscience Research, 2023)
Many scientists have expressed their opinion that language is a means of communication, and they have paid particular attention to the fact that communication expresses not only the logical content of information, but also the mental state and feelings of the person entering into communication. The language of the people, which differs sharply from the literary language and is usually based on the generalization of all existing language norms, is based on the rules of the style of free speech.